Pamięci Oleha Hirnego (5 VI 1960-24 XI 2020) - Mróz, Tomasz (1975- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A text devoted to dr. Oleg Hirnyy (5 VI 1960-24 XI 2020) and his text submitted to "In Gremium" in summer 2020.
Keywords: Hirrny, Oleh (1960-2020); wspomnienie